LITERATURE STUDY: FAMILY INTERPERSONAL COMMUNICATION AND ITS RELATIONSHIP WITH THE DEVELOPMENT OF CHILDREN’S MENTAL HEALTH - Andini Dwi Arumsari; Anthonio Rhenaldy Cristian; RR Putri Shafa Rahmania; Jihan Hanifah; Nur Azmi Azizah (P3I UMSurabaya, 2025)
Interpersonal communication within the family is a key factor influencing children’s mental health, as through daily interactions, children learn to manage emotions, shape behaviors, and develop psychological resilience. This study aims to comprehensively review the relationship between family interpersonal communication and children’s mental health through a literature study approach. The method used is library research by examining books, articles, and national as well as international scientific journals relevant to the topics of family communication and children’s psychological well-being. The findings indicate that positive interpersonal communication quality, characterized by self-disclosure, feedback, and shared meaning, significantly contributes to enhancing children’s psychological well-being. Empathic, supportive, and emotionally validating communication strengthens secure attachment, self-confidence, emotional regulation, and resilience against stress and social pressure. Conversely, closed, authoritarian, or unempathetic communication increases the risk of mental health issues such as anxiety, depression, and dysfunctional behavior. Therefore, healthy interpersonal communication within the family serves as a fundamental foundation for developing children’s mental health and overall well-being in the future.